1990
DOI: 10.1111/j.1558-5646.1990.tb03816.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation Among Chewing Louse Populations (Mallophaga: Trichodectidae) in a Pocket Gopher Contact Zone (Rodentia: Geomyidae)

Abstract: Genetic variation among populations of chewing lice (Geomydoecus actuosi) was examined in relation to chromosomal and electrophoretic variation among populations of their hosts (Thomomys bottae) at a contact zone. Louse demes were characterized by low levels of genetic heterozygosity (H̄ = 0.039) that may result from founder effects during primary infestation of hosts, compounded by seasonal reductions in louse population size. Louse populations sampled from different hosts showed high levels of genetic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 24 publications
2
55
3
Order By: Relevance
“…Thus, a Wahlund effect may account for some of the heterozygote deficiency in the pooled Bur samples (infrapopulations from different farms) where allelic frequencies at the PGDH locus were markedly different. A Wahlund effect has been observed previously for other pooled population samples of ascaridoid species (Nadler, 1986) (1) and absence (0) of RAPD markers among individual Ascaris suum (333-442) grouped by locality and infrapopulation. Marker size is indicated beneath each primer number.…”
Section: Rapd Data and Comparative Analysis Of Markerssupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, a Wahlund effect may account for some of the heterozygote deficiency in the pooled Bur samples (infrapopulations from different farms) where allelic frequencies at the PGDH locus were markedly different. A Wahlund effect has been observed previously for other pooled population samples of ascaridoid species (Nadler, 1986) (1) and absence (0) of RAPD markers among individual Ascaris suum (333-442) grouped by locality and infrapopulation. Marker size is indicated beneath each primer number.…”
Section: Rapd Data and Comparative Analysis Of Markerssupporting
confidence: 58%
“…saline, and maintained for up to 24 hr at 37 C prior to dissection. For each host, entire ascaridoid infrapopulations were collected, an infrapopulation = all parasites of a single species from an individual host (Margolis et al, 1982 Homogenization of tissue samples for protein electrophoresis was performed as described previously (Nadler, 1986). Separate tissue homogenates of muscle and gonad (ovary or testis) were prepared for each individual, and both tissue types were used initially to survey various enzymatic loci.…”
mentioning
confidence: 99%
“…This suggests that even though the total Dennyus louse populations are larger than the host populations (each bird having on average two lice), the transmission dynamics of the parasites may result in a lower effective population size for the lice. Nadler et al (1990) found low levels of heterozygosity in gopher louse demes and differentiation among populations of lice resident on different individual hosts from the same host population. They suggested that the lice may undergo founder events with each initial infection of a juvenile gopher.…”
mentioning
confidence: 85%
“…At the same time, it presents an opportunity for further insight into the dynamics of the gopher-louse association. It would be of great interest to know how the phylogenies of the lice found on these gophers relate to the allozyme and mitochondrial trees for these gophers (see also Nadler et al, 1990). I should note that the broad concordance between allozyme, DNA, and morphological studies of gophers and lice (Hafner and Nadler, 1988;1990;Page et al, 1995) suggest that the trees shown in Figure 1 are indeed reasonable estimates of organismal phylogeny.…”
Section: Likelihood Testmentioning
confidence: 95%